ANALISIS FAKTOR YANG MEMENGARUHI IBU PASANGAN USIA SUBUR (PUS) YANG TIDAK MELAKUKAN PEMERIKSAAN PAP SMEAR UNTUK DETEKSI DINI KANKER SERVIKS DI RUMAH SAKIT UMUM HAJI MEDAN TAHUN 2014 - darmaisuri harahap; Erna Mutiara; Yusniwarti Yusad (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Cervical cancer is a kind of dangerous tumor that found in cervical area which can cause death to women in Indonesia. In the Medan Hajj General Hospital from October to December of 2013 there were 722 mothers of productive-age couples who visited to do health check at the obstetrics poly, only 4 (0.5%) mothers performed pap smears check. This research aimed to reduce variables that influenced mothers of productive-age couples who did not do the pap smear check as the cervical cancer early detection at Medan Hajj General Hospital period October- December 2013. Data were analyzed by using exploratory factor analysis. Mothers of productive-age couples who did not do pap smear check were the population of this research and were being sample numbered 80 mothers. Data were collected by interviewing using questionnaire. The result of data analysis showed that out of 8 variables (knowledge, attitude, culture, economic, education, husband's support, trust and fear) after being analyzed it formed two (2) factors namely factor 1 (knowledge, education, attitude economic and trust) as internal factors and factor 2 (culture, husband's support, and fear) as external factors. It is suggested for future studies that will use factor analysis method should increase the number of variables which will be reduced/summarized. Key word : productive-age couples, cervical cancer, factor analysis, Pap Smear